Household Incidence of Pollution Control Policies: A Robust Welfare Analysis Using General Equilibrium Effects - Araar, Abdelkrim; Dissou, Yazid; Duclos, Jean-Yves (Université d'Ottawa | University of Ottawa, 2008)
This study assesses the incidence of pollution control policies on households. In contrast to previous studies, we employ an integrated framework combining a multisector general equilibrium model with a stochastic dominance analysis using household-level data. We consider three policy instruments in a domestic emission trading system: (i) an output-based allocation of permits (OBA); (ii) the use of the proceeds of permit sales to reduce payroll taxes (RPT); (iii) and the use of these proceeds to reduce consumption taxes instead(UCS). The general equilibrium results suggest that the return to capital is more negatively affected than the wage rate in all simulations, since polluting industries are capital intensive. Abstracting from pollution externalities, the dominance analysis allows us to conclude that all three policies have a normatively robust negative (positive) impact on welfare (poverty). Formal dominance tests indicate that RPT first-order welfare dominates OBA over all values of household incomes. UCS also first-order poverty dominates RPT for any choice of poverty line below $CAN 18,600, and for any poverty line at the second order. Finally, while the three pollution control policies do not have a numerically large impact on inequality (in comparison to the base run), statistical tests indicate that inequality increases statistically more with OBA and RPT than with UCS. / Cet article évalue l'incidence des politiques de lutte contre la pollution sur le bien-être des ménages. Contrairement aux études précédentes, nous utilisons une approche intégrée combinant un modèle d'équilibre général multisectoriel avec une analyse de dominance stochastique basée sur des données de ménages. Nous considérons trois instruments de politique dans le cadre d’un système d'échange de droits d'émission: (i) une allocation de permis basée sur la production (OBA), (ii) l'utilisation du revenu de vente des permis pour réduire la taxe sur la masse salariale (RPT), (iii) et l'utilisation des revenus pour de réduire la taxe sur la consommation (UCS). Les résultats du modèle d'équilibre général suggèrent que la rémunération du capital est plus affectée que le salaire dans toutes les simulations étant donnée la forte intensité capitalistique des industries polluantes. Abstraction faite des externalités créées par la pollution, l’analyse de dominance nous permet de conclure que les trois politiques ont, sur un plan normatif, de façon robuste un impact négatif (positif) sur le bien-être (la pauvreté). Les tests formels de dominance en bien-être indiquent que RPT domine au premier ordre OBA pour toutes les valeurs de revenus des ménages. UCS domine également au premier ordre RPT pour tout seuil de pauvreté inférieur à $ CAN 18600, et au second rang pour tout seuil de pauvreté. Enfin, alors que les trois politiques de lutte contre la pollution n'ont pas un grand impact sur l'inégalité (en comparaison à la situation de référence), les tests statistiques indiquent que l'inégalité augmente de façon significative plus avec OBA et RPT que avec UCS.
Keywords: Pollution control policies; household incidence; stochastic dominance; general equilibrium effects; Politique de contrôle de la pollution; incidence sur les ménages; dominance stochastique; effets d’équilibre général